Pengaruh Self-Brand Image Congruity Terhadap Customer Brand Engagement Di Mediasi Oleh Brand-Relationship Quality : (Studi Kasus Smartphone Xiaomi) - Komang Tri Werthi; Gede Suwardika; Sri Wahyuni. M (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2024)
This study aims to analyze the effect of self-brand image congruity on customer- brand engagement mediated by brand-relationship quality as an intervening variable in the Xioami smartphone case study. The dependent variable analyzed in this study is customer-brand engagement. The independent variable analyzed in this study is self- brand image congruity. The samples used in this study were Xioami smartphone users consisting of 100 respondents. Sampling was carried out using the accidental sampling method, which is an accidental sampling method by taking cases or respondents who happened to be available or available somewhere according to the research context. This study uses the Structural Equation Modeling (SEM) analysis method. The results of this study indicate that self-brand image congruity has a positive and significant effect on brand-relationship quality. Brand-relationship quality has a positive and significant effect on customer-brand engagement. Self-brand image congruity has no positive and significant effect on customer-brand engagement. The other results of this study are that self-brand image congruity has a positive and significant effect on customer-brand engagement through brand-relationship quality as an intervening variable.